2019
DOI: 10.3390/jcm8091340
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte Injury in Lupus Nephritis

Abstract: Systemic lupus erythematosus (SLE) is characterized by a broad spectrum of renal lesions. In lupus glomerulonephritis, histological classifications are based on immune-complex (IC) deposits and hypercellularity lesions (mesangial and/or endocapillary) in the glomeruli. However, there is compelling evidence to suggest that glomerular epithelial cells, and podocytes in particular, are also involved in glomerular injury in patients with SLE. Podocytes now appear to be not only subject to collateral damage due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 108 publications
0
29
0
Order By: Relevance
“…Podocytes are epithelial cells with a well-developed cytoskeleton that are essential for the proper working of the glomerular filtration barrier in the kidneys [ 73 ]. Several alterations have been observed in the podocytes of lupus nephritis patients, which contribute to proteinuria and kidney damage [ 74 ]. Importantly, calcineurin acts on different podocyte signaling pathways, which contribute to kidney damage.…”
Section: Calcineurin Role and Characterizationmentioning
confidence: 99%
“…Podocytes are epithelial cells with a well-developed cytoskeleton that are essential for the proper working of the glomerular filtration barrier in the kidneys [ 73 ]. Several alterations have been observed in the podocytes of lupus nephritis patients, which contribute to proteinuria and kidney damage [ 74 ]. Importantly, calcineurin acts on different podocyte signaling pathways, which contribute to kidney damage.…”
Section: Calcineurin Role and Characterizationmentioning
confidence: 99%
“…4 Although LP is not grouped in the classification of LN of the ISN/RPS 2003, 5 a review article in 2019 proposed grouping LP in the classification. 6 Here, we report a rare case of LP at the onset of SLE.…”
mentioning
confidence: 90%
“…Several studies of podocyte injury in LN found that podocyte injury correlated with the degree of proteinuria, and renal outcome. 46 Morphologically these podocyte injuries are similar to minimal change disease or focal segmental glomerulosclerosis (FSGS). These biopsies show extensive podocyte injury, without evidence of IC deposition.…”
Section: Lupus Nephritis Pathophysiologymentioning
confidence: 99%